2022
DOI: 10.3390/economies10070163
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of the Entrepreneurial Conditions on Economic Growth: Evidence from OECD Countries

Abstract: This study aims to assess the impacts of entrepreneurial framework conditions on economic growth based on the level of economic development in transition-driven economies and innovation-driven economies. The data were organised into a panel (2000–2019) and obtained from the National Expert Survey (NES), the Global Monitor Entrepreneurship (GEM), and the World Bank. By applying the generalised method of moments (GMM) estimation, we found that R&D transfer has a negative impact on economic growth that is inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 90 publications
0
4
1
2
Order By: Relevance
“…Nowadays, industrial development, its modernization as well as sustainable development are considered solutions to ensure the dynamic development of society as a whole (Gomes et al, 2022;Verdugo & Wright, 2020). Therefore, it can be said that technological innovation, science, investment in infrastructure are the basis for achieving sustainable industrial development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nowadays, industrial development, its modernization as well as sustainable development are considered solutions to ensure the dynamic development of society as a whole (Gomes et al, 2022;Verdugo & Wright, 2020). Therefore, it can be said that technological innovation, science, investment in infrastructure are the basis for achieving sustainable industrial development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Крім того, підприємці комерціалізують інновації і, отже, виводять на ринок нові та вдосконалені продукти та послуги. Це може мати трансформаційний вплив на економічні та соціальні умови, можливо, на краще [5]. Незважаючи на очевидну важливість підприємництва для національних економік, все ще існує потреба у розумінні впливу підприємницької діяльності на суб'єктивне благополуччя націй.…”
Section: оцінка впливу активної підприємницької діяльності на рівень ...unclassified
“…The authentic foundations of entrepreneurship derive from the economic sciences, whose functional approaches focus a priori on the effects of entrepreneurship and the role of the entrepreneur in the development of the economic system, aiming to understand the personality traits, behavior, origins, motivation and trajectory of the entrepreneur from a social point of view (Gomes et al, 2022). Entrepreneurship is also the ability of starting up and developing an activity that gives life to a project, of which the individual him/herself is the initiator.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, some of the loan received by entrepreneurs does not bear fruit. Many researchers in the existing literature have tried to predict whether or not a person can be granted loan based on certain criteria and characteristics of the person using machine learning (ML) (Guan et al, 2023;Noriega et al, 2023;. Unfortunately, the literature review revealed that there is a lack of research based on the prediction of loan fructification by entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%